1987
DOI: 10.1177/00220345870660050401
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Photoelectron Spectroscopic Studies of the Adsorption of Salivary Constituents on Enamel

Abstract: Time-dependent change of adsorption of salivary components on the outermost surface layer of enamel was studied by x-ray photoelectron spectroscopy. Adsorption of proteinaceous components, as monitored in terms of the relative mass of nitrogen, was detected within 30 min, increased with time, and reached a plateau at 90 min. Thus, the ratio of nitrogen to calcium in the two-hour sample increased to about 240 times that in the control sample. The ratio of carbon to nitrogen on the surface decreased to about one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 14 publications
4
16
0
Order By: Relevance
“…Fur thermore, calcium and phosphorous signals remain in approximately the same P/Ca concentration ratios after adsorption, but in reduced absolute intensities which suggests either that thick adsorbed layers al most fully cover the enamel surface, possibly contain ing small cracks, or that at least under high vacuum conditions the adsorbed layers are very thin, within the range of the XPS information depth. The elemen tal surface concentration ratios of enamel after in vitro adsorption of proteins from clarified human whole saliva are in remarkable agreement with recent results from Kuboki et al [1987], studying adsorption of salivary constituents on enamel by putting enamel slabs in the mouth of subjects for 30-120 min, fol lowed by thorough rinsing. This agreement between in vivo and in vitro results on salivary protein adsorp tion demonstrates the validity of our method to han dle saliva and the adsorption setup as a whole.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Fur thermore, calcium and phosphorous signals remain in approximately the same P/Ca concentration ratios after adsorption, but in reduced absolute intensities which suggests either that thick adsorbed layers al most fully cover the enamel surface, possibly contain ing small cracks, or that at least under high vacuum conditions the adsorbed layers are very thin, within the range of the XPS information depth. The elemen tal surface concentration ratios of enamel after in vitro adsorption of proteins from clarified human whole saliva are in remarkable agreement with recent results from Kuboki et al [1987], studying adsorption of salivary constituents on enamel by putting enamel slabs in the mouth of subjects for 30-120 min, fol lowed by thorough rinsing. This agreement between in vivo and in vitro results on salivary protein adsorp tion demonstrates the validity of our method to han dle saliva and the adsorption setup as a whole.…”
Section: Discussionsupporting
confidence: 89%
“…This clearly indicates a calcium deficiency, corresponding with the data of Kuboki et al [1987]. Although Arends et al [1979] argued that the outer 10-20 nm of the enamel surface is Ca deficient (1.40 < C a/P < 1.45), the Ca deficiency generally obtained in XPS studies is much greater and (according to the sample prepara tion in this study) extending to deeper parts of the en amel.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Pellicle formation reaches a plateau 60-90 min after exposure of a cleaned tooth surface to the oral environment [Sønju and Rølla, 973;Kuboki et al, 1987]. More recent studies have confirmed that pellicle formation is a fairly rapid process reaching a maximum after approximately 30-60 min depending on the secretion studied [Lamkin et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…1 The thickness of the pellicle generally reaches a plateau after 30-90 min. [2][3][4] The pellicle layer is of great importance since it participates in all the interfacial events taking place at the tooth surface, such as de-and remineralisation, lubrication and bacterial adherence. Indeed, the pellicle can act as a semi-permeable membrane and modulate the demineralisation of enamel.…”
Section: Introductionmentioning
confidence: 99%